Modifikasi Metode Newton-Steffensen Bebas Turunan - M. Nizam M.Y (UIN Sultan Syarif Kasim Riau, 2015)
This paper develops Newton-Steffensen method involving Lagrange interpolation and the divideddifference to eliminate the derivative function and increase the order of convergence. Based of thisresearch is showed that the modified produce five-order convergence with efficiency index 54 1,49531 .Simulation numerical are given to illustrate the efiiciency and performance of the new methods in solvingnonlinier equations.Keywords: Interpolation, Newton-Steffensen, Nonlinear Equations, Order of Convergence,